Relaxation and Diffusion in Complex Systems - Ngai, K.L.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Relaxation and Diffusion in Complex Systems comprehensively presents a variety of experimental evidences of universal relaxation and diffusion properties in complex materials and systems. The materials discussed include liquids, glasses, colloids, polymers, rubbers, plastic crystals and aqueous mixtures, as well as carbohydrates, biomolecules, bioprotectants and pharmaceuticals. Due to the abundance of experimental data, emphasis is placed on glass-formers and the glass transition problem, a still unsolved problem in condensed matter physics and chemistry. The evidence for universal properties of relaxation and diffusion dynamics suggests that a fundamental physical law is at work. The origin of the universal properties is traced to the many-body effects of the interaction, rigorous theory of which does not exist at the present time. However, using solutions of simplified models as guides, key quantities have been identified and predictions of the universal properties generated. These predictions from Ngai$1 (Bs Coupling Model can qualitatively as well as quantitatively explain the experimentally observed dynamic properties of different complex interacting materials and systems in many cases, essentially from the strength of the interaction. Change of relaxation and diffusion dynamics when dimension of the material is reduced to nanometer scale are consistent with the predictions. The success of the Coupling Model provides some measure of understanding the relaxation properties of complex interacting systems and also paves the way for the construction of rigorous theories in the future. Relaxation and Diffusion in Complex Systems describes advances that affect many different areas of research, and will be of particular interest to those working in the fields of materials science, nanotechnology, energy and medicine.s
Introduction -- Universal Relaxation and Diffusion Properties in Complex Systems -- Experimental Evidences -- Computer Simulations -- Theoretical Modeling and Interpretations -- Many-Body Relaxation Dynamic and Relation to Chaos -- Glass Transition and the Glassy State -- Role of Thermodynamics, Volume, Entropy and Temperature -- Polymer Viscoelasticity -- Ionic Conductivity Relaxation in Ionically Conducting Materials -- Relaxation and Diffusion at Nanometer Scales -- Relaxation in Biomolecules.
Keywords: Physics; Engineering; Physics; Phase Transitions and Multiphase Systems; Ceramics, Glass, Composites, Natural Methods; Complexity